Tafsir Surah Al-Lahb Perspektif Fakhr al-Din al-Razi dan Krisis Spiritual Masyarakat Kontemporer - Nisa Ghina Raudhatul Janah; Rian Hidayat; Jainah; Cecep Cecep Zakarias El Bilad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Palangkaraya, 2026)
Spiritual crisis in contemporary society is characterized by tendencies toward materialism, hedonism, and the loss of meaning in life, which impact inner anxiety and moral degradation. This condition raises the question of how the interpretation of the Qur’an can provide a response to such a crisis. This study aims to examine the interpretation of Surah Al-Lahb in Mafātīḥ al-Ghayb by Fakhr al-Din al-Razi and its relevance to the phenomenon of spiritual crisis in contemporary society. This research employs a qualitative approach with a library research method, using the Qur’an and the commentary (tafsir) of Mafātīḥ al-Ghayb as primary sources, supported by various related literatures. Data were analyzed using a descriptive-analytical method with a thematic (maudu’i) approach. The results of the study show that Surah Al-Lahb not only contains a condemnation of Abu Lahab as a historical figure but also conveys universal theological and ethical messages, such as criticism of arrogance, dependency on material wealth, and the rejection of truth. In a contemporary context, the figure of Abu Lahab represents modern humans who are trapped in worldly orientations and experience spiritual emptiness. This indicates that the interpretation of Surah Al-Lahb is relevant both as a reflection and a conceptual solution to overcome spiritual crises by emphasizing the importance of balance between material aspects and the values of faith in life.